Recent changes in chironomid communities and hypolimnetic oxygen conditions relate to organic carbon in subarctic ecotonal lakes - Luoto, Tomi P.; Rantala, Marttiina V.; Kivilä, E. Henriikka; Nevalainen, Liisa (Science of The Total Environment, 2020)
A key question in aquatic elemental cycling is related to the influence of bottom water oxygen conditions in regulating the burial and release of carbon under climate warming. In this study, we used head capsules of Chironomidae larvae to assess community and diversity change between the past (estimated as Pre-Industrial Period) and present and to reconstruct changes in hypolimnetic oxygen conditions from 30 subarctic ecotonal lakes (northeastern Lapland) using the top-bottom paleolimnological approach applying surface sediment (topmost 0-2 cm) and reference (4-5 cm) samples. Subsequently, we tested the findings against dissolved organic carbon (DOC) concentration of the sites. We found that the benthic communities were statistically dissimilar between the past and the present with largest changes occurring in the more transparent oligo-mesohumic lakes. However, murky polyhumic lakes displayed uniformly a decrease in diversity. The chironomid-inferred oxygen values showed a general decrease toward the present with largest shifts in low-DOC lakes, whereas no significant changes were found in the hypolimnetic oxygen conditions of high-DOC lakes, which were often located in wet-land areas. These finding suggest that lakes associated with constant organic carbon inputs are more resilient toward climate-induced reductions in hypolimnetic oxygen. (c) 2018 Elsevier B.V. All rights reserved. Peer reviewed